(untitled) (Research, Society and Development, 2023)
The Integrative and Complementary Practices in Health encourage multidisciplinary work, welcoming the pharmacist for his clinical assignments. In this way, the objective of the present study was to present, through a literature review, the performance of the pharmaceutical professional in face of integrative and complementary practices. The present study is a narrative review of the literature in which national and international bibliographic searches were used. This review presents a qualitative approach of a basic nature with an exploratory objective. Searches were carried out in databases such as: LILACS, MedLINE and SciELO. Integrative and Complementary Practices – PICs, are therapies that stimulate the body’s mechanisms for prevention and recovery of health, resulting from effective and safe technologies. Among the health professionals qualified to work in these practices are pharmacists. The pharmacist’s role extends to guidance services and support measures for therapy, cooperating for the individual’s well-being and, consequently, preventing various illnesses, such as chronic diseases, thus contributing to self-care, promotion and health conservation. The review showed that the pharmacist has a fundamental role in the integration of these practices into the clinical context, participating in several stages, from the selection of herbal medicines, for example, to the orientation and follow-up of the patient. Through a holistic view, the pharmacist can assess the interaction between conventional and integrative therapies, contributing to a more comprehensive and personalized approach to patient care.